The Role of Parents in Developing Early Childhood Independence Based on Islamic Values within the Family Environment - Istiqlaliyah, Hulailah; Indriyani, Fitri (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2025)
Early childhood independence is a fundamental aspect of personality and social development. In Muslim families, Islamic values play a central role in shaping children's character and fostering independence. This study aims to explore the role of parents in promoting early childhood independence through the application of Islamic values within the family environment. A qualitative case study approach was employed, utilizing observation, in-depth interviews, and documentation as data collection techniques. The findings reveal that parents play a significant role as role models, facilitators, and mentors in instilling Islamic values such as amanah (trustworthiness), shiddiq (truthfulness), istiqamah (consistency), and sabr (patience). These findings are supported by developmental theories from Erikson, Piaget, and Vygotsky, as well as Islamic educational perspectives from scholars such as Ibn Khaldun and Imam Al-Ghazali. This study highlights the importance of synergy between family-based education and Islamic values in holistically fostering independence in early childhood.